Assessment of MIR200B Polymorphisms Association with Sight-Threatening Diabetic Retinopathy - Niloufar Zal; Sare Safi; Hamid Ahmadieh; Sahba Fekri; Sajad Najafi; Ali Forouhari; Afrooz Moghaddasi; Majd Hejazi; Bahareh Kheiri; Maryam Eslami; Fatemeh Suri (Journal of Current Ophthalmology)
Purpose: To assess the possible association between MIR200B variations and sight-threatening diabetic retinopathy (STDR). Methods: A total number of 141 diabetes mellitus patients were enrolled in the study and divided into two groups including 76 patients diagnosed with STDR assigned to the case group, and 65 subjects without STDR considered in the control group. Peripheral blood specimens were used to extract the DNA content, and the primary MIR200B encoding sequence was amplified using a polymerase chain reaction. Then, the amplified DNA was sequenced by the Sanger method. The sequences were compared to the MIR200B reference sequence to find sequence variations. RNAfold, miRVaS, and Mfold bioinformatics web servers were employed to predict the potential effects of the identified variations on RNA structure. Results: Two MIR200B gene variants were identified. Although both variations were found more frequent in cases than controls, statistical analysis of allelic and genotypic features did not reach statistical significance. Conclusions: In silico analysis showed mild changes in MIR200B secondary structure and increased free energy in the presence of one of the identified variants (g.1167183G>A; rs72563729). Increasing the sample size in future studies may help a more accurate interpretation of the allelic association of MIR200B variations with STDR.